SUPPORT VECTOR MACHINE ANALYSIS FOR INTEREST AND TALENT CLASSIFICATION WITH PYTHON LIBRARY - Devi Sartika; Febie Elfaladonna; Andre Mariza Putra (STMIK Royal, 2024)
Abstract: Recognizing one's interests and talents early on is crucial in guiding an individual toward a prosperous future. While distinct, interests and talents share a close relationship. Interest denotes a genuine attraction to something without external pressure, and when consistently nurtured, it evolves into a skill or talent. Machine learning, specifically utilizing the SVM algorithm with the RBF kernel, can be applied to categorize interests and talents. Prior to SVM modeling, conducting Exploratory Data Analysis (EDA) is imperative for scrutinizing interests and talents. This analysis facilitates the identification of variables, enabling the elimination of missing values and ensuring the selection of appropriate interest and talent variables. The primary objective is to achieve optimal accuracy in modeling the classification of interests and talents. The insights gained from this research contribute to the creation of an application designed for categorizing interests and talents within SDN XYZ school. This application is designed for student use, assisting them in making informed decisions about their future education and career paths Keywords: exploratory data analysis; interests and talents; machine learning; SVM Algorithm Abstrak: Mengenali minat dan bakat seseorang sejak dini sangat penting dalam membimbing individu menuju masa depan yang sukses. Meskipun berbeda, minat dan bakat memiliki hubungan yang erat. Minat mengindikasikan ketertarikan yang tulus terhadap sesuatu tanpa tekanan eksternal, dan ketika terus-menerus dibina, berkembang menjadi keterampilan atau bakat. Pembelajaran mesin, khususnya dengan menggunakan algoritma SVM dan kernel RBF, dapat digunakan untuk mengelompokkan minat dan bakat. Sebelum pemodelan SVM, melakukan Analisis Data Eksploratif (EDA) sangat penting untuk mengkaji minat dan bakat. Analisis ini memfasilitasi identifikasi variabel, memungkinkan penghilangan nilai yang hilang, dan memastikan pemilihan variabel minat dan bakat yang tepat. Tujuan utamanya adalah mencapai akurasi optimal dalam pemodelan klasifikasi minat dan bakat. Temuan dari penelitian ini berkontribusi pada pengembangan aplikasi yang ditujukan untuk mengkategorikan minat dan bakat di sekolah SDN XYZ. Aplikasi ini dirancang untuk digunakan oleh siswa, membantu mereka membuat keputusan yang terinformasi mengenai pendidikan dan karier masa depan mereka. Kata kunci: Algoritma SVM; exploratory data analysis; machine learning; minat dan bakat